Sporting and tourist activities: legal aspects - Katja Sontag; Frédérique Roux (Revue de Géographie Alpine)
The outdoors has become, in a few decades, the playground of millions of practitioners. This evolution has been accompanied by the increasingly pronounced presence of law in the organisation and practice of outdoor sports. There has consequently been a significant “law-making process” in relation to these activities. This latter, in the first instance, has consisted in the application of classic legal tools (contract law, tort, administrative authority). But rapidly it became necessary to adopt regulations relating to these activities. “Sports law” was the first to emerge. We observe today an increasing number of technical rules specific to outdoor sports, and to specific activities. As such these activities have been submitted to the growing complexity of the legal system and applicable law, which, difficult to interpret, has become a source that is confusing, contradictory and of very considerable legal insecurity. The adoption of the sports code is an attempt to restore this situation to order.